Outbound as the Alternative Method to Have Fun Arabic Learning - Jauhar Ali (ALSINATUNA, 2018)
As muslims, we understand that Arabic language is very urgent for the development and improvement of our religious knowledge and practices. Many muslim students have willingness to master the language to be able to communicate and understand religious texts, which are mostly written in Arabic. Most of them, however, are not interested in Arabic language class, due to the difficulties in terms of pronunciation, reading, and writing. Understanding the expressions and grammatical features (al-Nahwu and Al- Sharf) are the other challenges that the students cannot handle in short time and the themes are boring. In brief, there is an assumption that studying Arabic is difficult.The questions, then, are how to change the assumption?, and what are the best method and strategy for students in studying the language in an enjoyable, fun, and supportive atmosphere? These questions show both reality and challenge, especially for the Arabic language teachers and lecturers, that there is a need to change the conventional teaching of Arabic language and at the same time, to find a new method and real actions to answer the above questions. This article offers a new method of teaching which focuses not only on teaching of Arabic language but also enjoyable, fun, and full of spirit atmosphere. The method is called by “outbound using fun games” or “outbound fun games”